Distinct immune responses of juvenile and adult oysters (Crassostrea gigas) to viral and bacterial infections. (December 2016) - Green, Timothy; Vergnes, Agnes; Montagnani, Caroline; Lorgeril, Julien
Abstract Since 2008, massive mortality events of Pacific oysters (Crassostrea gigas ) have been reported worldwide and these disease events are often associated with Ostreid herpesvirus type 1 (OsHV-1). Epidemiological field studies have also reported oyster age and other pathogens of theVibrio genus are contributing factors to this syndrome. We undertook a controlled laboratory experiment to simultaneously investigate survival and immunological response of juvenile and adultC. gigas at different time-points post-infection with OsHV-1, Vibrio tasmaniensis LGP32 andV. aestuarianus . Our data corroborates epidemiological studies that juveniles are more susceptible to OsHV-1, whereas adults are more susceptible toVibrio . We measured the expression of 102 immune-genes by high-throughput RT-qPCR, which revealed oysters have different transcriptional responses to OsHV-1 andVibrio . The transcriptional response in the early stages of OsHV-1 infection involved genes related to apoptosis and the interferon-pathway. Transcriptional response toVibrio infection involved antimicrobial peptides, heat shock proteins and galectins. Interestingly, oysters in the later stages of OsHV-1 infection had a transcriptional response that resembled an antibacterial response, which is suggestive of the oyster's microbiome causing secondary infections (dysbiosis-driven pathology). This study provides molecular evidence that oysters can mount distinct immune response to viral and bacterial pathogens and these responses differ depending on the age of the host.